Epidemiology, Clinical Features and Treatment Outcome of Wilms' Tumor in Taiwan: A Report from Taiwan Pediatric Oncology Group - 洪悠紀(Iou-Jih Hung); 張琬惠(Wan-Hui Chang); 楊兆平(2 Chao-Ping Yang); 江東和(Tang-Her Jaing); 梁德城(Der-Cherng Liang); 林凱信(Kai-Hsin Lin); 林東燦(Dong-Tsamn Lin); 蕭志誠(Chih-Cheng Hsiao); 謝玉琳(Yuh-Lin Hsieh); 陳建旭(Jiann-Shiuh Chen (Journal of the Formosan Medical Association, 2004)
Taiwan Pediatric Oncology Group (TPOG)-W-91 is the first multi-institutional Wilms' tumor study for children in Taiwan. This clinical trial used a multidisciplinary approach, based on and similar to the National Wilms' Tumor Study 4. The study was conducted to evaluate the epidemiological characteristics and analyze the outcome of Wilms' tumor patients treated with this protocol. Ninety eight children with Wilms' tumor (WT) were analyzed for distributions of age, gender, associated congenital anomalies, tumor sites, histology, tumor weights, and clinical stages. Patients received individualized multimodality treatment based upon the histology of the tumor and clinicopathologic stage. The treatment included surgery, radiotherapy and 2-, 3-, and 4-agent active chemotherapeutic agents. Seventy patients were eligible for analysis of treatment outcome. The endpoints were progression-free and overall survival (PFS, OS). Patients were divided into various subgroups according to the chemotherapy regimen used, tumor stage, age at diagnosis, gender, and tumor weight. The prognostic factors were evaluated and the survival rates of various clinical subgroups were compared using log-rank test. The average annual incidence rate of WT was 2.9 per million children under 15 years of age. The M/F ratio was 1.04. The mean age at diagnosis was 3.7 years. All bilateral tumors occurred in females. Congenital anomalies were present in 17.3% of patients. Anaplastic histology was found in 6 of 98 cases (6.1%). The stage distribution was: I, 43.2%; II, 19.3%; III, 23.9%; IV, 6.8%; and V, 6.8%. The median follow-up time was 89.1 months (range, 1.8 to 128.1 months). The 5-year PFS rate was 0.7841 (SE, 0.0494; 53 of 70 patients) and the 5-year OS rate was 0.886 (SE, 0.038; 63 of 70 patients). Gender was found to be the only significant prognostic variable. This study evaluated the epidemiological characteristics, clinical features, multimodality therapy regimens, and treatment outcome of WT in Taiwan. Data obtained from this study may lead to further improvement in the prognosis of pediatric malignant solid tumor.